Effect of NaOH and water contents on solidification of sodium silicate free geopolymer - Siyal, A.A. (Trans Tech Publications Ltd, 2014)
Geopolymers are fast setting binder materials possessing strength comparable with Portland cement. In this study solidification and bonding behavior of sodium hydroxide activated class F fly ash geopolymers were determined. Solidification was determined using Vicat apparatus and bonding behavior study was carried out using Fourier transform infrared spectroscopy (FTIR). The decrease in solidification time from 105 minutes to 90 minutes was observed when Na/Al ratio increased from 1 to 1.4. By changing liquid to solid (L/S) ratio from 0.154 to 0.231 initial and final setting times found to increase. FTIR results showed main peaks at 1000 cm-1 and 1432 cm-1 due to asymmetric stretching of Al-O/ Si-O bonds. Â© 2014 Trans Tech Publications, Switzerland.